The Effect of SIMDA Implementation and SAP Implementation on the Quality of Financial Statements: HR Competence as an Intervening Variable (Empirical Study on Central Maluku Regency Government) - Adri Gunawan; Ferry H. Basuki; Paul Usmany (PT Mattawang Mediatama Solution, 2024)
HR competencies. The sample used in this study was 52 respondents. The analysis tool used is Partial Least Square (PLS) with SmartPls 3.2.9 tool. The results of the study showed that the implementation of SIMDA and HR competence had a positive effect on the quality of financial statements while the implementation of SAP did not affect the quality of financial statements. The results also show that the implementation of SIMDA and SAP Implementation has a positive effect on HR competence. Furthermore, the results show that the implementation of SIMDA has a positive effect on the quality of financial statements through HR competence, and SAP implementation has a positive effect on the quality of financial statements through HR competence